2020
DOI: 10.21608/mb.2020.104708
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungal research in Egypt: Present status

Abstract: Plant endophytes are a potential source for the production of bioactive compounds that can fight against devastating diseases in both plants and humans. Among these endophytic microorganisms, endophytic fungi are one of the dominant group of microorganisms with a potential role in plant growth promotion and the discovery of noble bioactive natural products. Endophytic fungi possess several bioactivities like anticancer, antimicrobial, anti-rheumatoidal, insecticidal, plant growth stimulants, crop protection, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Indeed, the key parameters such as pH, agitation, airflow, dissolved oxygen, temperature, and feeding pumps were affected by large-scale production of microbial mass production [16,18]. Many studies have been reported to evaluate the cultivation parameters for Trichoderma sp., by using a submerged fermentation system to increase its bioactive metabolites as well as conidia [14][15][16][17]. To detect perfect conditions for transposing the cultivation of endophytic T. harzianum to the industrial scale, the batch and exponential fedbatch fermentation modes were applied in our work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the key parameters such as pH, agitation, airflow, dissolved oxygen, temperature, and feeding pumps were affected by large-scale production of microbial mass production [16,18]. Many studies have been reported to evaluate the cultivation parameters for Trichoderma sp., by using a submerged fermentation system to increase its bioactive metabolites as well as conidia [14][15][16][17]. To detect perfect conditions for transposing the cultivation of endophytic T. harzianum to the industrial scale, the batch and exponential fedbatch fermentation modes were applied in our work.…”
Section: Discussionmentioning
confidence: 99%
“…When the cultivation process was completed without adding any extra supplemented nutrition, this mode is called batch fermentation mode. The fed-batch fermentation mode was implemented to increase microbial biomass densities by feeding extra substrates and other supplements after a certain period of incubation time [ 15 ]. One of the most significant cereal grains that are grown in diverse weather conditions worldwide is barley ( Hordeum vulgare L) that belonged to the Poaceae family [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation